2022
DOI: 10.1146/annurev-genet-072920-041046
|View full text |Cite
|
Sign up to set email alerts
|

Genome Protection by DNA Polymerase θ

Abstract: DNA polymerase θ (Pol θ) is a DNA repair enzyme widely conserved in animals and plants. Pol θ uses short DNA sequence homologies to initiate repair of double-strand breaks by theta-mediated end joining. The DNA polymerase domain of Pol θ is at the C terminus and is connected to an N-terminal DNA helicase–like domain by a central linker. Pol θ is crucial for maintenance of damaged genomes during development, protects DNA against extensive deletions, and limits loss of heterozygosity. The cost of using Pol θ for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 136 publications
(196 reference statements)
0
19
0
Order By: Relevance
“…A key mediator of MMEJ is the DNA polymerase POLQ. Several POLQ inhibitors are being developed and are entering clinical trials as they demonstrate exciting anti-cancer potential 43 . Given that CCNF depletion- or EXO1 R842A mutation-mediated hyper-resection leads to defective MMEJ, exploiting the cyclin F-EXO1 pathway could be an alternative approach to POLQ inhibition to restrict MMEJ and, therefore, to sensitise cells to IR.…”
Section: Discussionmentioning
confidence: 99%
“…A key mediator of MMEJ is the DNA polymerase POLQ. Several POLQ inhibitors are being developed and are entering clinical trials as they demonstrate exciting anti-cancer potential 43 . Given that CCNF depletion- or EXO1 R842A mutation-mediated hyper-resection leads to defective MMEJ, exploiting the cyclin F-EXO1 pathway could be an alternative approach to POLQ inhibition to restrict MMEJ and, therefore, to sensitise cells to IR.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was suggested that Pol θ performs end trimming using the intrinsic endonuclease activity associated with the PD (repurposing of metal ions in the polymerase active site for endonucleolytic cleavage) [ 35 ]. However, in a further paper, an alternative explanation of the results was provided which made the authors doubt the existence of trimming endonuclease activity [ 5 ]. The PD structure lacks a potential endonuclease domain [ 11 ].…”
Section: Pol θ As a Central Player In Tmejmentioning
confidence: 99%
“…As it turned out, Pol θ cell functions are more diverse than previously expected. This unique enzyme is involved in a number of different DNA-related pathways reviewed in [ 4 , 5 , 6 , 7 , 8 ]. In this review, we discuss unique properties of Pol θ, its roles in the protection of genome stability and integrity as well as recent progress in studies of Pol θ as a target for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the candidates with strong possible cross reactivity could be the enzyme DNA polymerase theta (Polθ). The DNA polymerase Polθ has been described rather in detail 22–24 . From four established linear immune epitopes in CA I (DGLAV, NVGHS, SLKPI and SSEQL), the alignment with amino acid sequence of Polθ (https://www.uniprot.org/uniprotkb/O75417/entry#sequences) can be found in three of them: SLKPI, DGLAV and SSEQL.…”
Section: Cross Reactivity—a Possible Explanation?mentioning
confidence: 99%
“…The DNA polymerase Polθ has been described rather in detail. [22][23][24] From four established linear im- 25 The reverse transcriptase activity of Polθ has been shown in elegant experiments in Richard Pomerantz's lab. 26 Therefore, Polθ seems to be an ideal candidate for a cancer drug target.…”
Section: Cross Re Ac Tivit Y-a P Oss Ib Le E Xpl Anation?mentioning
confidence: 99%